Slight Pro-Inflammatory Immunomodulation Properties of Dendritic Cells by Gardnerella vaginalis: The “Invisible Man” of Bacterial Vaginosis? - Thomas Bertran; Patrick Brachet; Marjolaine Vareille-Delarbre; Julie Falenta; Annie Dosgilbert; Marie-Paule Vasson; Christiane Forestier; Arlette Tridon; Bertrand Evrard (Journal of Immunology Research)
Bacterial vaginosis (BV), the most common genital infection in reproductive-aged women, is associated with increased risk of sexually transmitted infections. Its etiology remains unclear, especially the role of Gardnerella (G.) vaginalis, an anaerobic bacterium characteristic of the BV-alteration of the vaginal ecosystem. In the genital mucosa, dendritic cells (DCs) sense bacteria of the microenvironment via receptors and then orchestrate the immune response by induction of different T cell subtypes. We investigated the interactions between G. vaginalis and human monocyte-derived DCs using a wide range of bacterial concentrations (multiplicity of infection from 0.01 to 100), and the effects of this pathogen on PHA-induced lymphocyte proliferation. As observed by electron microscopy and cytometry, G. vaginalis reduced the internalization ability of DCs by forming extracellular clusters and induced neither DC maturation, nor DC secretion of cytokines, except at the highest dose with a very early DC maturation state. The same profile was observed on lymphocytes with significant increases of proliferation and cytokine secretion only at the highest bacterial concentration. Our findings indicate that G. vaginalis possesses slight immune-stimulating activities against DCs and T cells, reflecting thus a defective inflammatory response and giving rise to the atypical, non- or low-grade, inflammatory clinical disease profile.